Internet-Based Parenting Interventions to Reduce Digital Addiction in Adolescents: A Systematic Review - Aluysius Hendra Wijaya; Mulya Virgonita; Shinta Pratiwi (Jurnal Impresi Indonesia, 2025)
Internet addiction has become a critical issue in the digital era, especially among adolescents who are exposed to technology from an early age. This study aims to understand the dynamics of external factors influencing digital addiction and to explore internet-based parenting strategies as a form of intervention. The method used was a Systematic Literature Review (SLR), analyzing eight relevant studies published between 2020 and 2025 that focused on internet addiction and parenting styles. Results indicate that negative emotions (such as depression and loneliness), low self-control, and social or family environments contribute significantly to digital addiction. Furthermore, dysfunctional parenting practices may create a recurring cycle of addiction within families. Online parenting interventions show promising potential in reducing such risks by enhancing parental knowledge, skills, and engagement in positive parenting practices. These findings highlight the importance of developing multicomponent and context-sensitive digital parenting strategies to combat digital addiction effectively